Reassessment of the threatened status of IUCN red listed Indian river shad Gudusia chapra (Hamilton, 1822) from Bangladesh (Dhaka University Journal of Biological Sciences, 2019)
The Indian river shad, Gudusia chapra, locally known as chapila fish is rich in nutritive values and important to artisanal and subsistence fisheries in Bangladesh. The conservation status of this species is of particular interest due to its recent decline in rivers. To assess the current status of this species in Bangladesh, we recorded its abundance at seven sites in the Padma, the Meghna and the Tetulia rivers during pre-monsoon, monsoon and post-monsoon seasons. In this study, G. chapra was consistently recorded in the study area and there was no significant temporal or spatial variation in its abundance. The observed mean length and weight of the species were similar to those recorded in earlier studies. Currently, G. chapra is listed as vulnerable species in the IUCN Red List of Threatened Species in Bangladesh. Although the primary known habitat of this species is river, IUCN assessment was based on production from beel and Kaptai Lake habitats. In this study, consistent occurrence and availability of the species across spatial and temporal scales in rivers suggest the necessity to reassess the conservation status of G. chapra in the country.Dhaka Univ. J. Biol. Sci. 28(1): 83-91, 2019 (January)